Measurement of the centrality and pseudorapidity dependence of the integrated elliptic flow in lead-lead collisions at $\sqrt{s_{NN}}=2.76$ TeV with the ATLAS detector - ATLAS collaboration (2862 authors) (2014)
The integrated elliptic flow of charged particles produced in Pb+Pb collisions at sqrt(s_NN)=2.76 TeV has been measured with the ATLAS detector using data collected at the Large Hadron Collider. The anisotropy parameter, v_2, was measured in the pseudorapidity range |eta| <= 2.5 with the event-plane method. In order to include tracks with very low transverse momentum pT, thus reducing the uncertainty in v_2 integrated over pT, a 1 mu b-1 data sample without a magnetic field in the tracking detectors is used. The centrality dependence of the integrated v_2 is compared to other measurements obtained with higher pT thresholds. A weak pseudorapidity dependence of the integrated elliptic flow is observed for central collisions, and a small decrease when moving away from mid-rapidity is observed only in peripheral collisions. The integrated v2 transformed to the rest frame of one of the colliding nuclei is compared to the lower-energy RHIC data.